Inhibition effect of NaHCO3 on the flame geometry and thermal properties of jet diffusion fire. (1st February 2023) - Wang, Yandong; Zhou, Kuibin; Ma, Xianzheng; Zhang, Ding
Highlights: A facility is designed to produce the propane-NaHCO3 jet diffusion flame. NaHCO3 power reduces the air entrainment and increases the flame height. NaHCO3 power decreases the flame temperature and radiative fraction. A model is proposed to predict the thermal radiation of propane-NaHCO3 jet flames. Abstract: Jet fires can frequently occur due to the accidental release of pressure vessel and pipe that store and convey gas fuel. Thus, it is of great interest to study a measure or technique to suppress the jet diffusion flame, for avoiding the domino effect in process industry. In this work, a facility designed for producing the gas–solid jet diffusion flame, was used to study the inhibition mechanism and effect of sodium bicarbonate (NaHCO3 ) power on the jet flame behavior. The NaHCO3 power of D 50  = 6.5 μm in size was used for test. A review of chemical inhibition mechanism of NaHCO3 was conducted for the propane combustion, which can help to explain the variation of propane jet flame behavior with the addition of NaHCO3 . The experimental result and theoretical analysis show that the NaHCO3 power increases the flame height but significantly decreases the flame temperature and radiative fraction. In particular, the jet flame is extinguished when the mass ratio of NaHCO3 power to propane gas increases to be over 2.12. In addition, the line source radiation model is proposed to predict the radiant heat flux of the jet diffusion flame with NaHCO3 power.